Association of Immunohistochemical Expression of P53 in Pancreatic Ductal Adenocarcinoma - Tariq, Hassan; Ameer, Amna; Khan, Wajahat Ahmed; Naqvi, Syed Rehan Asghar; Rizwan, Saba; Humayun, Saba (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the immunohistochemical expression of p53 in pancreatic ductal adenocarcinoma and chronic pancreatitis. Study Design: Comparative cross-sectional study. Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi, Pakistan from Jul 2020 to Jun 2022. Methodology: Our study inducted 116 individuals in total (56 with cancer and 60 with pancreatitis). Following the recovery of the cases, each block was divided into sections and stained with hematoxylin-eosin and p53 antibodies. Microsoft Excel 2010 was used for the statistical analysis. Results: Out of the 116 cases studied, 56 cases were found to be adenocarcinoma. Among these cases, 42(75%) showed p53 positivity according to the Sophia scoring system, with +3 and +4 staining considered positive. Of these 56 cases, 3 cases were scored 1+, 11 cases were scored 2+, 21 cases were scored 3+, and 21 cases were scored 4+. 8 out of 60 cases (13.33%) of pancreatitis showed p53 positivity. Conclusion: The majority of pancreatic adenocarcinomas exhibit immunohistochemical overexpression of p53, which can be used in conjunction with other immunohistochemical markers to aid in the diagnosis of carcinoma and differentiate it from benign mimickers.